Potensi dan risiko taburia hati ayam sebagai upaya pencegahan stunting dan defisiensi vitamin A pada balita - Wahyu Vera Wardani; Risa Hadi; Nadiyah Rahma Fauziyah; Muhammad Zakaria (Poltekkes Kemenkes Aceh, 2025)
Background: Chicken liver as a cheap and easily available source of protein requires research into its nutritional content and safety levels to support optimal growth for toddlers.Objectives: To analyze nutritional content (water content, ash content, protein content, fat content, carbohydrate content, beta carotene), metal contamination (Pb and Cu), microbial contamination (TPC) in fresh chicken liver samples and chicken liver powder.Methods: This research design is experimental. There are 2 samples for this research, namely fresh chicken liver samples and chicken liver powder. Chicken liver taburia is a sample of chicken liver that has undergone a boiling and drying process. This research used 3 repetitions. Sample preparation was carried out at the Food Processing Laboratory, Cirebon Muhammadiyah University on March 15 2024. The nutritional content that observed were water content, ash content, protein content, fat content, carbohydrate content, beta carotene, heavy metal contamination (Pb and Cu), microbial contamination (TPC). Analysis of nutrients and contaminants at Chem Mix Laboratory Yogyakarta on April 6 2024. The statistical test carried out was the independent t test. Results: All components of nutritional content analysis (moisture content, ash content, protein content, fat content, carbohydrate content, beta carotene), heavy metal contamination (Pb and Cu), microbial contamination (TPC) in fresh chicken liver samples and chicken liver taburia has a significant difference with p value = 0,000. Conclusion: Chicken liver powder has a higher nutritional content than fresh chicken liver (except water content). Heavy metal contamination (Pb and Cu), microbial contamination (TPC) in both samples were within safe limits.